Effect of Pulmonary Rehabilitation on Postoperative Clinical Status in Patients with Lung Cancer and Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. (28th March 2022) - Wang, Lu; Yu, Mingwei; Ma, Yunfei; Tian, Rong; Wang, Xiaomin
Abstract : Pulmonary rehabilitation (PR) has a curative effect in patients undergoing pneumonectomy for lung cancer. Nevertheless, the contribution of PR to the clinical status of patients with chronic obstructive pulmonary disease (COPD) undergoing lung resection has not been adequately elucidated. The aim of this systematic review of randomized and nonrandomized controlled trials was to appraise the impact of PR compared to conventional treatment based on postoperative clinical status in patients with lung cancer and COPD. Literature in English from PubMed, Cochrane Library, Science Citation Index, and Embase databases and in Chinese from the Chinese National Knowledge Infrastructure and the WANFANG Database was retrieved from inception to November 2021, employing the keywords "Pulmonary Neoplasms, " "Chronic Obstructive Pulmonary Diseases, " "Physical Therapy Modalities, " and "pulmonary rehabilitation." Only studies that reported PR results were included. This review was registered in the International Prospective Register of Systematic Reviews (number: CRD42021224343). A total of nine controlled trials with 651 patients were included. Postoperative pulmonary complications (PPCs) were the primary outcome measure. PR decreased the risk of complications after surgery compared to regular treatment (odds ratio (OR) 0.21, 95% confidence interval (CI) 0.12–0.37, P < 0.01 ). PR reduced the risk of pneumonia after surgery compared to regular treatment (OR 0.36, 95% CI 0.15–0.86, P = 0.02 ). There was a significant difference in the postoperative length of stay (mean difference −2.13 days, 95% CI −2.65 to −1.61 days, P < 0.05 ). PR was an effective intervention that decreased PPCs in patients suffering from lung cancer and COPD. However, due to the limitations of the available data, the results should be interpreted with caution.